Determining the optimal antioxidant strategy: a comparative analysis of extractionmethods in Cistus villosus L. extracts revealed by LC-HRMS and computational modeling - Bouakkaz H.; Erol E.; Benarous K.; Topçu G.; Mahfoudı R.; Djerıdane A.; Yousfı M. (My University, 2025)
Background/aim: Cistus villosus L., a beloved tea herb, contains a treasure trove of potent antioxidants. Our research unveils this ancient ally’s potential to shield against oxidative stress, a modern health threat. Materials and methods: Antioxidant assays were conducted to evaluate the potency of ethyl acetate extract. IC50 values were determined for the extract in various antioxidant assays. Furthermore, molecular docking was employed for the examination of the 22 compounds analyzed through LC-HRMS. Additionally, ADMET and PASS investigations were conducted to evaluate their capability as antioxidants and inhibitors of oxidant formation. Results: Each identified compound boasts a history of antioxidant prowess, building the natural defense arsenal of C. villous. Antioxidant assays showed the potency of the ethyl acetate fraction with an IC50 value of 5.30 mg/L in the DPPH• test, which is better than that of the studied standard, α-tocopherol (36.35 mg/L). The pharmacokinetic profiles demonstrated good properties for the identified compounds. The PASS study unveiled their potential as antioxidants, and molecular docking showed their effectiveness as inhibitors of oxidant formation in the human body by blocking the studied targets. Conclusion: This herb, a timeless testament to nature’s bounty, stands poised to become a powerful weapon in our fight against oxidative stress, promising a future of natural well-being.
Keywords: Eczacılık; Temel Eczacılık Bilimleri; Analitik Kimya; Sağlık Bilimleri; Pharmacology and Therapeutics; Basic Pharmaceutics Sciences; Analytical Chemistry; Health Sciences; Klinik Tıp (Med); Yaşam Bilimleri (Life); Farmakoloji Ve Toksikoloji; Farmakoloji Ve Eczacılık; Clinical Medicine (Med); Life Sciences (Life); Pharmacology & Toxicology; Pharmacology & Pharmacy; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Yaşam Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Life Sciences